Internacionalization via sandeich doctoral: experience report in the leading country of scientific production - Ekuni, Roberta (Universidade Estadual de Campinas, 2019)
In Brazil, most of the scientific production is carried out by post-graduate students. Internationalization as the fourth pillar of the university encourages international cooperation and programs for students to spend a period of internships abroad. The present experience report aims to report the experience of a doctoral internship at Washington University in Saint Louis, focusing on research, teaching and extension activities. For the description of the experience, a descriptive analysis of the experience was used for the period from March to August of 2017. As a result we identified: more opportunities for discussion of the research in an interdisciplinary way, the amount of resources invested for research and the relation between Teachers and teaching, research and extension activities. It is hoped that the present report may clarify and encourage more Brazilian researchers to participate in this type of internship program abroad that enables both cultural experience and learning as well as academic growth, and encouraging the adoption of similar practices in our universities, taking into account the limitations of this experience.